Multimodality Fusion with MRI, CT, and Ultrasound Contrast for Ablation of Renal Cell Carcinoma - Hayet Amalou; Bradford J. Wood (Case Reports in Urology)
Fusion technology with electromagnetic (EM) tracking enables navigation with multimodality feedback that lets the operator use different modalities during different parts of the image-guided procedure. This may be particularly helpful in patients with renal insufficiency undergoing kidney tumor ablation, in whom there is a desire to minimize or avoid nephrotoxic iodinated contrast exposure. EM tracking software merges and fuses different imaging modalities such as MRI, CT, and ultrasound and can also display the position of needles in real time in relation to preprocedure imaging, which may better define tumor targets than available intraoperative imaging. EM tracking was successfully used to ablate a poorly visualized renal tumor, through the combined use of CT, gadolinium-enhanced MR, and contrast-enhanced US imaging to localize the tumor.